2012
DOI: 10.1002/dev.21017
|View full text |Cite
|
Sign up to set email alerts
|

Malleability in the development of spatial reorientation

Abstract: After becoming disoriented, organisms must re-establish their position in space. The core knowledge position argues that reorientation relies only on extended 3D surfaces, and that this sensitivity operates automatically and is innately present. In contrast, the adaptive combination perspective argues that reorientation is experience-expectant and malleable, and depends on both extended 3D surfaces and 2D feature cues. We test these divergent views by comparing young (Experiment 1) and mature (Experiment 2) C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…It is possible that navigation behavior results from a process of weighting one's own sense of orientation, and the information conveyed by beacons, according to one's experience of their past usefulness in similar situations, as envisaged by adaptive combination theories of decision-making (see Footnote 1). The findings of a new controlled-rearing experiment on mice provide suggestive support for this possibility (Twyman, Newcombe & Gould, in review). In this experiment, mice who were raised in a rectangular environment encoded and used the shapes of testing environments automatically in disoriented search tasks, providing evidence that they, like normally reared animals and animals raised in environments devoid of both geometry and features (Brown et al, 2007; Chiandetti & Vallortigara, 2008), reoriented by layout geometry and used their sense of orientation to find the hidden object.…”
Section: Discussionmentioning
confidence: 94%
“…It is possible that navigation behavior results from a process of weighting one's own sense of orientation, and the information conveyed by beacons, according to one's experience of their past usefulness in similar situations, as envisaged by adaptive combination theories of decision-making (see Footnote 1). The findings of a new controlled-rearing experiment on mice provide suggestive support for this possibility (Twyman, Newcombe & Gould, in review). In this experiment, mice who were raised in a rectangular environment encoded and used the shapes of testing environments automatically in disoriented search tasks, providing evidence that they, like normally reared animals and animals raised in environments devoid of both geometry and features (Brown et al, 2007; Chiandetti & Vallortigara, 2008), reoriented by layout geometry and used their sense of orientation to find the hidden object.…”
Section: Discussionmentioning
confidence: 94%
“…Although there were no significant differences in the acquisition of geometric information alone, the circular-reared mice were faster to learn a feature panel task. Additionally, and crucially, on a test of incidental geometry encoding (a rectangle with a feature panel marking the correct location), results showed that the rectangular-reared mice had encoded the geometry, while the circular-reared mice had not (Twyman, Newcombe, & Gould, 2013).…”
Section: Adaptive Combination Theorymentioning
confidence: 97%
“…Although there were no differences in the acquisition of geometric information alone, the circular-reared mice were faster to learn a feature panel task. Additionally, and crucially, on a test of incidental geometry encoding (a rectangle with a feature panel marking the correct location), the rectangular-reared mice had encoded the geometry while the circular-reared mice had not (Twyman, Newcombe, & Gould, 2012).…”
Section: Rearing Effectsmentioning
confidence: 99%